Attenuation of extubation responses: Comparison of prior treatment with verapamil and dexmedetomidine - Mistry, Tuhin; Purohit, Shobha; Arora, Gunjan; Gill, Nitesh; Sharma, Jaya (Journal of Neuroanaesthesiology and Critical Care, 2016)
Background: Tracheal extubation is almost always associated with stress response, airway response, and arrhythmias. There are many ways to attenuate this stress response. We have compared verapamil and dexmedetomidine on attenuation of these responses. Materials and Methods: Thirty patients (American Society of Anaesthesiologists Grade I, II) scheduled for spinal surgeries under general anaesthesia were randomly divided into two groups. At the end of surgery, after return of spontaneous efforts (bispectral index >80), in “Group V” verapamil 0.1 mg/kg and in “Group D” dexmedetomidine 0.3 mcg/kg were administered as bolus intravenously over one minute. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were recorded just before (T0) and 2 min after intravenous administration of study medications (TM), just after oral suction (TS), immediately after extubation (TE) and 1, 3, 5 and 10 min postextubation (E1, E3, E5, E10). Duration of emergence and extubation, quality of extubation, Richmond Agitation Sedation Scale (RASS) score and time to reach modified Aldrete score ≥9 were compared. Results: HR, SBP, DBP, MAP were higher in Group V than Group D, but statistically insignificant (P > 0.05). Extubation quality scores was 1 for 20%, 2 for 60% and 3 for 20% patients in Group V, whereas 1 in 80%, 2 in 20% in Group D. There was occurrence of bradycardia within 2 min of administration of drug in one patient in Group D. RASS score was in the range of -1 to +1 in >90% patient in Group V, whereas -3 to -1 in 80% cases in Group D. Conclusion: Single dose of dexmedetomidine (0.3 mcg/kg) given before extubation produced significant attenuation of circulatory and airway responses during extubation as compared to verapamil (0.1 mg/kg).
Keywords: Dexmedetomidine; extubation responses; verapamil